(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article identifies the different scenic spaces occupied by the groups of Bumba-meu-Boi from Parnaiba, Piaui. They were hired to perform on the street, in front of the contractor’s residence. Twenty years ago, with the creation of São João da Parnaiba, artists directed their activity to prepare the competitive presentation that happens in quadrilhódromo. In 2020, due to the pandemic and the importance of respecting isolation, groups joined digital platforms and created presentations in this new space. It was discussed the views of the artists on these issues and how the space generated an increase in the number of players, a new spatial relationship between artists and the public, and presentations shorter than those that took place on the streets.